2023
DOI: 10.1002/jha2.663
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax with decitabine or azacitidine in the first‐line treatment of acute myeloid leukemia

Abstract: Treatment paradigms for acute myeloid leukemia (AML) have evolved at a rapid pace in recent years. The combination of venetoclax with a hypomethylating agent prolonged survival in clinical trials when compared to hypomethylating agent monotherapy. However, little is known about the performance of venetoclax‐based regimens outside of clinical trials, given conflicting safety and efficacy data. Even less is known about the impact of the hypomethylating agent backbone. In this study, we demonstrate that decitabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Regarding toxicity, neutropenia was the most common side effect in both treatment groups and was observed in the vast majority (90%) of our patients receiving HMAvenetoclax, in accordance with previously reported real-world data [24]. Anemia and thrombocytopenia were also very common, at a rate of 85% and 67.5%, respectively, slightly less than some previous real-world reports [24], but higher than notified in VIALE-A [7]. Although retrospectively documenting real-life data is less accurate than randomized trials, partially contributing to these differences, it is obvious from our and previous data that hematologic toxicity is one of the main handling issues during HMA-venetoclax treatment in AML.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding toxicity, neutropenia was the most common side effect in both treatment groups and was observed in the vast majority (90%) of our patients receiving HMAvenetoclax, in accordance with previously reported real-world data [24]. Anemia and thrombocytopenia were also very common, at a rate of 85% and 67.5%, respectively, slightly less than some previous real-world reports [24], but higher than notified in VIALE-A [7]. Although retrospectively documenting real-life data is less accurate than randomized trials, partially contributing to these differences, it is obvious from our and previous data that hematologic toxicity is one of the main handling issues during HMA-venetoclax treatment in AML.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding toxicity, neutropenia was the most common side effect in both treatment groups and was observed in the vast majority (90%) of our patients receiving HMAvenetoclax, in accordance with previously reported real-world data [24]. Anemia and thrombocytopenia were also very common, at a rate of 85% and 67.5%, respectively, slightly less than some previous real-world reports [24], but higher than notified in VIALE-A [7].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Second, the CCI score provides a convenient and clinically meaningful parameter to assess treatment candidates. We previously reported that a CCI score threshold of 7 identified high-risk patients treated with venetoclax and a hypomethylating agent in the front-line setting [7]. We hypothesized that a lower score threshold would apply to the relapsed or refractory setting due to the burden and complications of multiple treatment courses.…”
Section: Discussionmentioning
confidence: 99%
“…However, outcomes need to be clarified in the context of lower-intensity venetoclax-based strategies. Our group, among others, reported significant survival differences in unique molecular cohorts unaccounted for in ELN 2022, such as AML with mutated IDH1 or IDH2 [4][5][6][7]. Additionally, preclinical studies and updated analyses of clinical trials have suggested that signaling mutations are implicated in primary refractoriness or adaptive resistance to venetoclaxincluding mutations in FLT3, PI3K, and RAS, as shown in Figure 1 [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 86%